2014
DOI: 10.1155/2014/592627
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Selection of Machining Parameters in Multipass Turnings Using Firefly Algorithm

Abstract: Determination of optimal cutting parameters is one of the most important elements in any process planning of metal parts. In this paper, a new optimization technique, firefly algorithm, is used for determining the machining parameters in a multipass turning operation model. The objective considered is minimization of production cost under a set of machining constraints. The optimization is carried out using firefly algorithm. An application example is presented and solved to illustrate the effectiveness of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Basically, the idea was to switch fireflies with best values of objective function; actually, firefly's crossover is implemented. Firefly at position l, from population 1, replaces firefly at position k in population 2 and vice versa, firefly at position k from population 2 comes at position l in population 1 (Algorithm 2lines 36,37,38). This crossover of fireflies allows population with worse solutions to get into space of better solutions, while the population with better solutions checks if the global minimum is found, or there is even better solution to search for.…”
Section: Post Processing and Results Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Basically, the idea was to switch fireflies with best values of objective function; actually, firefly's crossover is implemented. Firefly at position l, from population 1, replaces firefly at position k in population 2 and vice versa, firefly at position k from population 2 comes at position l in population 1 (Algorithm 2lines 36,37,38). This crossover of fireflies allows population with worse solutions to get into space of better solutions, while the population with better solutions checks if the global minimum is found, or there is even better solution to search for.…”
Section: Post Processing and Results Presentationmentioning
confidence: 99%
“…Venkata Rao and Kalyankar 4 used teaching-learning-based optimization algorithm (TLBO) for operation of multi-pass turning and proved that a lower number of iterations is required for convergence to the optimal solution. Belloufi et al 37 used Firefly algorithm (FA) and hybrid genetic algorithm-sequential quadratic programming (GA-SQP) 38 and obtained lower numerical values of production cost compared with other techniques, but without satisfying all constraints. Srinivas et al 8 applied particle swarm optimization (PSO) and provided a detailed comparison of the exceeded constraints found in ACO, 12 GA 7 and SA-PS.…”
Section: Literature Overviewmentioning
confidence: 99%
“…They concluded that the TLBO can converge to the optimal solution within a lower number of iterations. Belloufi et al [21] proposed a Firefly Algorithm (FA), but constraint limitation such as cutting force was incorrectly handled.…”
Section: Introductionmentioning
confidence: 99%
“…The optimization framework was based on the optimization model proposed by Agapiuou [3]. The same algorithm was later applied by Belloufi et al [10] for determination of optimized conditions in a multipass turning process. The optimization problem was formulated so as to achieve minimization of production cost under a set of machining constraints.…”
Section: Introductionmentioning
confidence: 99%